PENGARUH PEMBERIAN MAKANAN TAMBAHAN TERHADAP PENINGKATAN BERAT BADAN IBU HAMIL KEK (KURANG ENERGI KRONIS) DI WILAYAH KERJA PUSKESMAS LABUAN LOMBOK - Anak Agung Sagung Putri Chandradewi (poltekkes kemenkes mataram, 2015)
Abstract: The gestation period is the period that determines the quality of children born. State of poor maternal nutrition before pregnancy and during pregnancy tend to give birth to babies with low birth weight, even the possibility of the baby died. This study aims to determine the effect of supplementary feeding on maternal weight gain less energy chronic health centers in the region of Labuan Lombok East Lombok. This research is conducted is eksperime apparent in society, using Quasi- Experimental design ( QE ) : Non- Equivalent Control Group Design. The sample in this study is a chronic lack of energy pregnant women, respectively 15 pregnant women less chronic energy for the treatment group and the control group. The provision of supplementary food such as biscuits given to the treatment group for 90 days. Additional foods such as biscuits containing energi474,75 given kcal and 17.4 grams of protein, made using local food base material soybean, corn flour, wheat flour, sugar, margarine/oil, eggs and skim milk. The type of data collected is weight, consumption of nutrients (energy, protein), and the contribution of supplementary feeding on energy consumption and total protein as well as the effect of supplementary feeding of weight gain in pregnant women less chronic energy dinalisis with statistical test